Rancang Bangun Alat Pengering Daun Kelor Otomatis berbasis Arduino Uno - Okyranida, Indica Yona; Astuti, Irnin Agustina Dwi (UNIVERSITAS INDRAPRASTA PGRI, 2023)
Moringa (Moringa oleifera) is a plant native to the tropical and subtropical regions of South Asia, but it has spread to various regions worldwide. Traditionally utilized for food, medicinal, and agricultural purposes, the moringa plant offers diverse benefits from all its parts. Moreover, moringa is also employed in agriculture due to its ability to thrive in tropical and subtropical environments and its tolerance to poor soil conditions. Moringa leaves are often used as an additional ingredient in traditional Indonesian cuisine and boast remarkable health potential. However, knowledge on how to process moringa leaves remains limited among the general populace.The drying process of moringa leaves, a common processing method, is often carried out traditionally using direct sunlight. However, this method presents challenges such as contamination risks, difficulty in controlling temperature and humidity, and potential degradation of nutrient content and product quality. Hence, the development of an automated moringa leaf drying device based on Arduino Uno offers an effective solution with automatic control of temperature, humidity, and safety features, ensuring the production of high-quality products efficiently and safely. Despite having some drawbacks, ongoing innovation is essential to enhance the performance and sustainability of moringa leaf drying devices in the future